PENGARUH HARGA EKSEKUSI DAN ESOP TERHADAP KINERJA PERUSAHAAN DENGAN MODERASI KEPEMILIKAN MANAJERIAL - Budiman, Arip; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to find out the influence of exercise price and employee stockownership program to the company performance which is moderated by managerial ownership.Thesample selection has been done by using purposive sampling method on go public companies whichare listed in Indonesia Stock Exchange (IDX) with the selected criteria i.e. go public company whichhas financial statement during 2012-2015 periods, go public company which has done ESOP during2012-2015 periods. Based on the research method, 47 go public companies have been selected assamples. The data analysis has been done by using SPSS 23rd version statistics test instrument.Theresult of the research shows that employee stock ownership program gives positive influence to thecompany performance and employee stock ownership program gives negative influence to thecompany performance which is moderated by managerial ownership whereas exercise price does notgive any significant influence to the company performance and exercise price does not give anysignificant influence to the company performance which is moderated by managerial ownership.Keywords:Exercise price, employee stock ownership program, company performance, managerialownership